Monte Carlo dosimetric study of the Flexisource Co-60 high dose rate source - Vijande, Javier; Granero, Domingo; Perez-Calatayud, Jose; Ballester, Facundo (Journal of Contemporary Brachytherapy, 2012)
Purpose : Recently, a new HDR 60Co brachytherapy source, Flexisource Co-60, has been developed (Nucletron B.V. Veenendaal, The Netherlands). This study aims to obtain dosimetric data for this source for its use in clinical practice as required by AAPM and ESTRO. Material and methods : Two Monte Carlo radiation transport codes were used: Penelope2008 and GEANT4. The source was centrally-positioned in a 100 cm radius water phantom. Absorbed dose and collisional kerma were obtained using 0.01 cm (close) and 0.1 cm (far) sized voxels to provide high-resolution dosimetry near (far from) the source. Dose rate distributions obtained with the two Monte Carlo codes were compared. Results and Discussion : Simulations performed with those two radiation transport codes showed an agreement typically within 0.2% for r > 0.8 cm and up to 2% closer to the source. Detailed results of dose distributions are being made available. Conclusions : Dosimetric data are provided for the new Flexisource Co-60 source. These data are meant to be used in treatment planning systems in clinical practice.